2013
DOI: 10.1155/2013/230487
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging Probes for Diagnosis and Therapy Evaluation of Breast Cancer

Abstract: Breast cancer is a major cause of cancer death in women where early detection and accurate assessment of therapy response can improve clinical outcomes. Molecular imaging, which includes PET, SPECT, MRI, and optical modalities, provides noninvasive means of detecting biological processes and molecular events in vivo. Molecular imaging has the potential to enhance our understanding of breast cancer biology and effects of drug action during both preclinical and clinical phases of drug development. This has led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 95 publications
1
24
0
Order By: Relevance
“…The contribution of the over-expressed HER1 (EGFR) in the enhanced cell-proliferation in breast cancer by binding to the epidermal growth factor (EGF) or the transforming growth factor alpha (TGFα) was also reported by Meng et al Therefore, antibody-based, affibody-based, or EGF-based molecular probes for EGFR imaging of breast cancer have been under investigation [53].…”
Section: Her-1 (Egfr) and Igf-1 Receptor Imagingmentioning
confidence: 86%
See 2 more Smart Citations
“…The contribution of the over-expressed HER1 (EGFR) in the enhanced cell-proliferation in breast cancer by binding to the epidermal growth factor (EGF) or the transforming growth factor alpha (TGFα) was also reported by Meng et al Therefore, antibody-based, affibody-based, or EGF-based molecular probes for EGFR imaging of breast cancer have been under investigation [53].…”
Section: Her-1 (Egfr) and Igf-1 Receptor Imagingmentioning
confidence: 86%
“…Some preliminary studies also showed that IGF-1R-targeted therapy in breast cancer can be monitored by imaging of IGF-1R expression [53,54]. …”
Section: Her-1 (Egfr) and Igf-1 Receptor Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Coupled with partial volume effect this may lead to a deterioration in detecting smaller "hot" lesions (while doing a skeletal scintigraphy or receptor scintigraphy in breast cancer 7 or in imaging the sentinel lymph node 8 or an underestimation of "cold" regions (brain, heart 9 ). In the case of a homogeneous tissue structure (e.g.…”
Section: Attenuation Correctionmentioning
confidence: 99%
“…Various antibodies have been proposed as suitable targeting ligands for conjugation with breast cancer molecular imaging probes. For instance, radiolabeled transtuzumab and pertuzumab antibodies targeting the HER2 cellular receptor entered clinical trials as imaging probes for PET and single photon emission computed tomography (SPECT) imaging modalities 26. Moreover, anti‐epidermal growth factor receptor (anti‐EGFR) and anti‐vascular endothelial growth factor receptor (anti‐VEGFR) antibodies conjugated with fluorescent nanoparticles and ultrasound contrast agents, respectively, have been assessed 27, 28.…”
Section: Tnbc: Strategies For Diagnosis and Treatmentmentioning
confidence: 99%